Cell-free oxidized hemoglobin drives reactive oxygen species production and pro-inflammation in an immature primary rat mixed glial cell culture - Agyemang, Alex Adusei; Kvist, Suvi Vallius; Brinkman, Nathan; Gentinetta, Thomas; Illa, Miriam; Ortenlöf, Niklas; Holmqvist, Bo; Ley, David; Gram, Magnus (Journal of neuroinflammation, 2021)
Background Germinal matrix intraventricular hemorrhage (GM-IVH) is associated with deposition of redox active cell-free hemoglobin (Hb), derived from hemorrhagic cerebrospinal fluid (CSF), in the cerebrum and cerebellum. In a recent study, using a preterm rabbit pup model of IVH, intraventricularly administered haptoglobin (Hp), a cell-free Hb scavenger, partially reversed the damaging effects observed following IVH. Together, this suggests that cell-free Hb is central in the pathophysiology of the injury to the immature brain following GM-IVH. An increased understanding of the causal pathways and metabolites involved in eliciting the damaging response following hemorrhage is essential for the continued development and implementation of neuroprotective treatments of GM-IVH in preterm infant. Methods We exposed immature primary rat mixed glial cells to hemorrhagic CSF obtained from preterm human infants with IVH (containing a mixture of Hb-metabolites) or to a range of pure Hb-metabolites, incl. oxidized Hb (mainly metHb with iron in Fe 3+ ), oxyHb (mainly Fe 2+ ), or low equivalents of heme, with or without co-administration with human Hp (a mixture of isotype 2-2/2-1). Following exposure, cellular response, reactive oxygen species (ROS) generation, secretion and expression of pro-inflammatory cytokines and oxidative markers were evaluated. Results Exposure of the glial cells to hemorrhagic CSF as well as oxidized Hb, but not oxyHb, resulted in a significantly increased rate of ROS production that positively correlated with the rate of production of pro-inflammatory and oxidative markers. Congruently, exposure to oxidized Hb caused a disintegration of the polygonal cytoskeletal structure of the glial cells in addition to upregulation of F-actin proteins in microglial cells. Co-administration of Hp partially reversed the damaging response of hemorrhagic CSF and oxidized Hb. Conclusion Exposure of mixed glial cells to oxidized Hb initiates a pro-inflammatory and oxidative response with cytoskeletal disintegration. Early administration of Hp, aiming to minimize the spontaneous autoxidation of cell-free oxyHb and liberation of heme, may provide a therapeutic benefit in preterm infant with GM-IVH.